Persistent organic pollutant lindane degradation by alkaline cold-brew green tea. (October 2019) - Wang, Chi-Wei; Chang, Shu-Chi; Liang, Chenju
Abstract: The environmental persistence of hazardous organochlorine pesticides (OCPs) such as lindane has resulted in a need for the development of reliable remediation technology for the removal of OCPs. Green tea extract/Fe 2+ under alkaline conditions is a potential green chemistry technology proven to be effective in reducing lindane. This study investigated the feasibility of directly using green tea leaves (GT-leaf) or cold-brew tea solution (GT-sol) with Fe 2+ additives at (bi)carbonate buffered pH 10 to treat lindane in the aqueous phase. The polyphenol was gradually released in the GT-leaf system and reached a similar concentration as that in the GT-sol system (∼800 mg L −1 at pH 6.5). Based on the analytical results of lindane degradation byproducts, it was recognized that the reductive mechanism acts as a major pathway and alkaline hydrolysis is a minor pathway. However, physical adsorption rapidly removes lindane from the GT-leaf system. A comprehensive evaluation of lindane degradation, chlorobenzene formation, degradation kinetics, and chloride liberation were conducted for the alkaline GT-sol/Fe 2+ system. The nonlinear simulations of the models developed showed good fits, with R 2 > 0.96. This study highlights the potential for GT-sol/Fe 2+ systems to remediate OCPs contamination. Graphical abstract: Image 1 Highlights: Green tea polyphenols/Fe 2+ at alkaline pH is able to degrade lindane. Tea leaves or cold-brew tea solution could be an effective source of polyphenols. Adsorption and reduction occur simultaneously in the green tea-leaf/Fe 2+ system. Lindane degradation in the green tea-solution/Fe 2+ system follows a reductive pathway. Chlorobenzene and Cl − are major byproducts and reaction kinetic models are derived.